When it all burns : fighting fire in a transformed world - Thomas, Jordan (Anthropologist) (Riverhead Books, 2025)
"An anthropologist and hotshot firefighter's gripping firsthand account of a record-setting fire season. Eighteen of California's largest wildfires on record have burned in the past two decades. Scientists recently invented the term "megafire" to describe wildfires that behave in ways that would have been impossible just a generation ago, burning through winter, exploding in the night, and devastating landscapes historically impervious to incendiary destruction. Wildland firefighters must navigate these new scales of destruction in real time. In When It All Burns, Jordan Thomas recounts a single, brutal six-month fire season with the Los Padres Hotshots-the special forces of America's firefighters. Being a hotshot is among the most difficult jobs on Earth. Their training is as grueling as any Navy SEAL's, and the social induction is even tougher. As Thomas viscerally renders his crew's attempts to battle flames that are often too destructive to contain, he uncovers the hidden cultural history of megafires. He investigates how a social system that prioritizes profit over people and nature has turned humanity's symbiotic relationship with wildfire into a war-and what can be done to change it back. Thomas weaves ecology and the history of indigenous oppression, federal forestry, and the growth of the fire industrial complex into an expansive, riveting narrative of a new phase in the climate crisis. Above all, he immerses readers in a story of friendship and community in the most perilous of circumstances, told with humor, humility, and affection"--